Unravelling the transcriptome of the human tuberculosis lesion and its clinical implications - Kaori L. Fonseca; Juan José Lozano; Albert Despuig; Dominic Habgood-Coote; Julia Sidorova; Diego Aznar; Lilibeth Arias; Álvaro Del Río-Álvarez; Juan Carrillo-Reixach; Aaron Goff; Leticia Muraro Wildner; Shota Gogishvili; et al. (Nature Communications)
Abstract The tuberculosis (TB) lesion is a complex structure, contributing to the overall spectrum of TB. We characterise, using RNA sequencing, 44 fresh human pulmonary TB lesion samples from 13 TB individuals (drug-sensitive and multidrug-resistant TB) undergoing therapeutic surgery. We confirm clear separation between the TB lesion and adjacent non-lesional tissue, with the lesion samples consistently displaying increased inflammatory profile despite heterogeneity. Using weighted correlation network analysis, we identify 17 transcriptional modules associated with TB lesion and demonstrate a gradient of immune-related transcript abundance according to spatial organization of the lesion. Furthermore, we associate the modular transcriptional signature of the TB lesion with clinical surrogates of treatment efficacy and TB severity. We show that patients with worse disease present an overabundance of immune/inflammation-related modules and downregulated tissue repair and metabolism modules. Our findings provide evidence of a relationship between clinical parameters, treatment response and immune signatures at the infection site.